Insights into the formation of konjac glucomannan gel induced by ethanol equilibration. (May 2022) - Tong, Cailing; Liu, Lu; Lin, Qingwei; Liu, Jingwen; Xue, Qingqing; Wu, Chunhua; Pang, Jie
Abstract: Alcogels have attracted increasing interest recently in the development of innovative semi-solid alcohol-containing products. The structural and physicochemical properties of konjac glucomannan (KGM) gels equilibrated in different ethanol concentrations were investigated. The swelling ratio of KGM gels increased with increasing KGM concentration and decreased with increasing ethanol concentration. All gels became stronger after ethanol equilibration; this may be due to the KGM chain aggregation when ethanol molecules gathered around KGM and the water molecules were pushed aside from the KGM chain, strengthening the gel. Increasing the ethanol concentration leads to decreased free water availability around the KGM chains and a more hydrophobic environment for KGM, resulting in a large amount of entanglement that facilitates the production of a local or continuous gel network structure, which was shown by the scanning electron microscopy images and low-field nuclear magnetic resonance results. Moreover, the amount of water was decreased, which was based on the peak related to the -OH bond in the KGM structure identified by Fourier transform infrared spectroscopy. The onset thermal decomposition temperatures of KGM gels equilibrated in solutions with various ethanol concentrations were higher than those of the control. The aggregation structures were altered, which was markedly dependent on ethanol concentration, constituting possible evidence of interactions upon equilibration. These results suggest that KGM gels under controlled concentrations of hydrocolloid and ethanol, have promising potential in developing innovative semi-solid alcohol-containing food products. Graphical abstract: Image 1 Highlights: Novel konjac glucomannan (KGM) alcogels equilibrated in different ethanol concentrations were prepared by a simple way. Microstructure and gel properties of KGM alcogels depended markedly on ethanol concentration. Ethanol increases hydrophobic interaction which improved the resultant KGM alcogel properties. Ethanol equilibration altered the aggregation structure and the moisture content of the KGM alcogels.